Extensive necrotizing fasciitis of scrotum and abdominal wall: Report of two cases and a review of the literature - Meng, Zhe; Wang, Yanchen; Chao, Jun; Ji, Yongjian; Sun, Yaofei; Zhu, Jiang; Gao, Tongbin; Chen, Si; Wang, Shenyang (Frontiers in Surgery, 2022)
The incidence rate of necrotizing fasciitis(NF) is low, and there is still a certain mortality after aggressive surgical debridement combined with broad-spectrum antibiotic treatment. Through retrospective analysis of two cases of large-scale NF of scrotum and abdominal wall treated in the Department of Urology of Weifang people's Hospital in January and April 2022, this paper analyzes and summarizes the scope of surgical debridement of NF, postoperative dressing changing skills, timing of multiple debridement, application and timing of vacuum sealing drainage(VSD), and the combined use of antibiotics. To provide experience for the clinical diagnosis and treatment of NF.